2010
DOI: 10.1007/s10803-010-1115-7
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Developing Spatial Frequency Biases for Face Recognition in Autism and Williams Syndrome

Abstract: The current study investigated whether contrasting face recognition abilities in autism and Williams syndrome could be explained by different spatial frequency biases over developmental time. Typically-developing children and groups with Williams syndrome and autism were asked to recognise faces in which low, middle and high spatial frequency bands were masked. All three groups demonstrated a gradual specialisation toward the mid-band. However, while the use of high spatial frequencies decreased in control and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 30 publications
4
26
1
Order By: Relevance
“…Piloting with children with ASD revealed that the very quick exposure was demotivating for them as they found it too difficult and that the 2-second exposure ensured that they received at least an equal amount of exposure to the face as the control group. In addition, when assessed by chronological age, individuals with autism presented a very similar pattern of results to the control group using these different exposure durations (Leonard et al, 2011), suggesting that differences in spatial frequency biases between the two groups in the current study are due to levels of functioning or nonverbal mental age and are not due to the differences in target duration.…”
Section: Methodssupporting
confidence: 55%
See 3 more Smart Citations
“…Piloting with children with ASD revealed that the very quick exposure was demotivating for them as they found it too difficult and that the 2-second exposure ensured that they received at least an equal amount of exposure to the face as the control group. In addition, when assessed by chronological age, individuals with autism presented a very similar pattern of results to the control group using these different exposure durations (Leonard et al, 2011), suggesting that differences in spatial frequency biases between the two groups in the current study are due to levels of functioning or nonverbal mental age and are not due to the differences in target duration.…”
Section: Methodssupporting
confidence: 55%
“…Each child was tested on a series of standardized and experimental tasks from Leonard et al (2011), including Raven's Standard Progressive Matrices (Raven, Raven, & Court, 2000), which was used as a measure of nonverbal mental age (NVMA) for both groups, and the Benton Test of Facial Recognition (Benton, Hamsher, Varney, & Spreen, 1983). Raven's Matrices are often used for matching purposes in the literature (Mottron, 2004) and are appropriate for a wide age range (Riby et al, 2008a).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The work by Dakin et al (34) reinterpreted numerosity processing in terms of the ratios between low and high spatial frequencies (LSF/HSF) in displays. Interestingly, individuals with WS have difficulty with LSF displays, and individuals with DS have problems with HSF displays (35,36). Irrespective of whether the numerical problems are directly in the HSF and LSF demands on the visual system and/ or related to differences in attention mechanisms, it is clear that the deficits and proficiencies of each syndrome (and perhaps, the different onset timing of small and large number discrimination in TD infants) do not entail an explanation solely in terms of domain-specific number abilities.…”
Section: Two Interpretations Of Infant Sensitivity To Number In Neuromentioning
confidence: 99%